The curious case of genome packaging and assembly in RNA viruses infecting plants - Ranjan, Tushar; Ranjan Kumar, Ravi; Ansar, Mohammad; Kumar, Jitesh; Mohanty, Auroshikha; Kumari, Anamika; Jain, Khushbu; Rajani, Kumari; Dei, Sailabala; Ahmad, Mohammad Feza (Frontiers in Genetics, 2023)
Genome packaging in plant viruses with RNA genome is an important step in the process of viral maturation. Viruses exhibit a remarkable degree of packaging specificity, despite the probability to co-package cellular RNAs. Till date, three types of viral genome packaging system are known. The recently upgraded type I packaging system, present in most of the small plant RNA viruses, involves nucleation and encapsidation of RNA genomes in an energy dependent manner. The type II and III packaging systems, found in phages and large DNA viruses, involve genome translocation and packaging inside the prohead by utilizing ATP. Although ATP is essential for all three packaging systems but each machinery employs unique mode of ATP hydrolysis and genome packaging mechanism. Plant RNA viruses cause various disease in crops and are responsible for huge economic losses. Understanding their mode of genome packaging and assembly is crucial for developing control strategies. Recent studies have revealed details of mechanism of genome packaging in type I system with special emphasis on small plant RNA viruses. The main focus of this study is to apprise readers with the technical breakthroughs that have facilitated the dissection of genome packaging and virion assembly processes in plant RNA virus.